Tropical and subtropical zones : resort design II - SHE, BEN (Dalian : Dalian li gong da xue chu ban she, 2013)
HardCover. Pub Date :2013-07-10 Pages: 513 Language: Chinese Publisher: Dalian University of Technology Press Basic information Title : Tropical and subtropical articles - Resort -II Price: 498 yuan Author: Publisher : Dalian University of Technology Press Publication Date: July 10. 2013 ISBN: 9787561180259 words: pages: 513 Edition : 1st Edition Binding: hardcover Size: weight : 4.1 Kg editor Summary Resort is an entertainment. leisure. relaxing place . but also a common resort hotel is part of a resort . Resort is not simply resort many years ago . it becomes even more special . Luxury in design is not necessary to be redefined luxury . comfort. practicality . and is designed to allow users to have an affinity for the key . Resorts Resorts embarking on any architectural design and interior decoration . start from the beginning with a blank canvas . World-class architecture...
engineering bookfair2015
Keywords: Resort architecture